Putrescine-functionalized carbon quantum dot (put-CQD) nanoparticle: A promising stress-protecting agent against cadmium stress in grapevine (Vitis vinifera cv. Sultana) - Panahirad, Sima; Dadpour, Mohammad Reza; Gohari, Gholamreza; Akbari, Ali; Mahdavinia, Gholamreza; Jafari, Hessam; Kulak, Muhittin; Alcázar, Rubén; Fotopoulos, Vasileios (My University, 2023)
Due to their sessile nature, plant cannot escape from stress factors in their growing environment, in either biotic or abiotic nature. Amid the abiotic stress factors; high levels of soil cadmium (Cd) impose heavy metal stress on plants, resulting in critical injuries and reduced agronomic performance. In order to buffer the adverse effects of Cd stress, novel nanoparticles (NP) have been applied and notable improvements have been reported. According to the literature, the protective roles of polyamines (e.g., Putrescine; Put) and carbon quantum dots (CQD) have been reported with respect to the plant productivity under either stress or non-stress conditions. Those reports led us to hypothesize that the conjugation of Put and CQD (Put-CQD NPs) might lead to further augmented performance of plants under stress and non-stress conditions. In this regard, we successfully synthesized a novel nanomaterial Put-CQD NPs. In this respect, Put (50 mg L−1), CQD (50 mg L−1) and Put-CQD NPs (25 and 50 mg L−1) were sprayed in ‘Sultana’ grapevines under Cd stress (10 mg kg−1). As expected, upon stress, Cd content in leaf and root tissues increased by 103.40% and 65.15%, respectively (p < 0.05). The high uptake and accumulation of Cd in plant tissues were manifested in significant alterations of physiological and biochemical attributes of the plant. Concerning stress markers, Cd stress caused increases in content of induced MDA, H2O2, and proline as well as electrolyte leakage rate. As expected, Cd stress caused critical reductions in fresh and dry leaf weight by 21.31% and 42.34%, respectively (p < 0.05). On the other hand, both Put-CQD NPs increased fresh and dry leaf weigh up to approximately 30%. The Cd-mediated disturbances in photosynthetic pigments and chlorophyll fluorescence were buffered with Put-CQD NPs. Of the defence system, enzymatic (SOD, APX, GP) as well as anthocyanin and phenolics were induced by both Cd stress and Put-CQD NPs (p < 0.05). On the other hand, Cd stress reduced content of polyamines (putrescine (Put), spermine (Spm) and spermidine (Spd) by 39.28%, 53.36%, and 39.26%, respectively (p < 0.05). However, the reduction levels were buffered by the treatments. Considering the effectiveness of both NP concentrations, the lower dose (25 mg L−1) could be considered as an optimal concentration. To our knowledge, this is the first report of its kind as a potential agent to reduce the adverse effects of Cd stress in grapevines.
Keywords: Abiotic stress; Functionalized nanoparticles; Heavy metals; Nano carriers; Polyamines